Comparative analysis of physiological variations and genetic architecture for cold stress response in soybean germplasm - Hussain, Muhammad Azhar; Li, Senquan; Gao, Hongtao; Feng, Chen; Sun, Pengyu; Sui, Xiangpeng; Jing, Yan; Xu, Keheng; Zhou, Yonggang; Zhang, Wenping; Li, Haiyan (Frontiers in Plant Science, 2023)
Soybean (Glycine max L.) is susceptible to low temperatures. Increasing lines of evidence indicate that abiotic stress-responsive genes are involved in plant low-temperature stress response. However, the involvement of photosynthesis, antioxidants and metabolites genes in low temperature response is largely unexplored in Soybean. In the current study, a genetic panel of diverse soybean varieties was analyzed for photosynthesis, chlorophyll fluorescence and leaf injury parameters under cold stress and control conditions. This helps us to identify cold tolerant (V100) and cold sensitive (V45) varieties. The V100 variety outperformed for antioxidant enzymes activities and relative expression of photosynthesis (Glyma.08G204800.1, Glyma.12G232000.1), GmSOD (GmSOD01, GmSOD08), GmPOD (GmPOD29, GmPOD47), trehalose (GmTPS01, GmTPS13) and cold marker genes (DREB1E, DREB1D, SCOF1) than V45 under cold stress. Upon cold stress, the V100 variety showed reduced accumulation of H2O2 and MDA levels and subsequently showed lower leaf injury compared to V45. Together, our results uncovered new avenues for identifying cold tolerant soybean varieties from a large panel. Additionally, we identified the role of antioxidants, osmo-protectants and their posttranscriptional regulators miRNAs such as miR319, miR394, miR397, and miR398 in Soybean cold stress tolerance.